2000
DOI: 10.1103/physrevb.61.6741
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy excitations of spin-Peierls chains with modified bond impurities

Abstract: The introduction of modified bond defects in spin-Peierls systems is investigated in a model of antiferromagnetic Heisenberg spin chains coupled to adiabatic phonons. Generically, new low-energy magnetic or nonmagnetic excitations appear below the bulk spin gap energy. When two adjacent bonds are modified, these excitations can be interpreted in terms of bound states of a soliton with the localized spin 1/2 located on the impurity site. It is shown that the confining potential occurs even in the case of isolat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In both cases the local magnetization is zero. When a non-magnetic defect is added to the chain, like an end-of-chain, the break in translational symmetry polarizes the spins around the defect [10][11][12][13][14][15][16][17][18][19][20][21]. While open chains in 1DQAFM have been studied in the past by magnetometry [22], and by NMR [23,24] due to the large spin orbit coupling and the difficulty to obtain high enough quality samples in metal oxide, very few EPR studies of end chain has been reported [25].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the local magnetization is zero. When a non-magnetic defect is added to the chain, like an end-of-chain, the break in translational symmetry polarizes the spins around the defect [10][11][12][13][14][15][16][17][18][19][20][21]. While open chains in 1DQAFM have been studied in the past by magnetometry [22], and by NMR [23,24] due to the large spin orbit coupling and the difficulty to obtain high enough quality samples in metal oxide, very few EPR studies of end chain has been reported [25].…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that the SCD doesn't see the counter anion but interact with 13 C. Regarding the spot at 1.2 MHz, This frequency is close to the Larmor frequency of 33 S (1.14 MHz) but in the limit of resolution. The natural abundance is very low (0.75%) but since we clearly observe 13 C nuclei, the detection of 33 S seems reasonable. However, we have to be aware of the possibility to detect 14 N which is highly abundant.…”
Section: B Pulsed Epr Spectroscopymentioning
confidence: 52%
“…( 2) for N = 13. The 2 13 = 8192 states are separated in S z sectors. One can see that the ground state is S z = 1/2 separated by a gap to several excited states S z = 1/2 and S z = 3/2 and then a quasi-continuum of states.…”
Section: Exact Diagonalizationmentioning
confidence: 99%
“…Even for the one-dimensional system, the A-type distortion is realized for weak randomness. 32) On the other hand, the B-type distortion is realized for strong randomness including bond dilution. Investigation of the situations of the two-dimensional system for which the B-type is realized will be an interesting subject of research.…”
Section: Summary and Discussionmentioning
confidence: 99%